2015
DOI: 10.1038/nrclinonc.2015.103
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in targeted therapies for hepatocellular carcinoma in the genomic era

Abstract: Mortality owing to liver cancer has increased in the past 20 years, and the latest estimates indicate that the global health burden of this disease will continue to grow. Most patients with hepatocellular carcinoma (HCC) are still diagnosed at intermediate or advanced disease stages, where curative approaches are often not feasible. Among the treatment options available, the molecular targeted agent sorafenib is able to significantly increase overall survival in these patients. Thereafter, up to seven large, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
528
2
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(543 citation statements)
references
References 155 publications
4
528
2
9
Order By: Relevance
“…Based on these results, a randomized phase III trial is currently comparing cabozantinib We agree that several reasons have potentially contributed to the failure of recent clinical trials [46]. In principle, even if the drug is active and effective, inadequate methodology and study design could be the reason for a negative result in a clinical trial.…”
Section: Cabozantinibmentioning
confidence: 98%
“…Based on these results, a randomized phase III trial is currently comparing cabozantinib We agree that several reasons have potentially contributed to the failure of recent clinical trials [46]. In principle, even if the drug is active and effective, inadequate methodology and study design could be the reason for a negative result in a clinical trial.…”
Section: Cabozantinibmentioning
confidence: 98%
“…In the process of liver cirrhosis, it is believed that chronic inflammation, continuous cycles of damage and regeneration, and the presence of etiology-specific carcinogens produce cumulative genetic derangements that are involved in the hepatocarcinogenic process. There are, on average, 30 to 40 mutations per liver tumor, and 5 to 8 of these are thought to be driver mutations (7). Several studies used deep genome sequencing to identify mutations in key genes thought to be involved in various pathways critical to normal cellular homeostasis, including telomerase reverse transcriptase (TERT) expression, chromatin remodeling, oxidative stress, cell cycle/TP53, Wnt/β-catenin, hepatic differentiation, growth factor/angiogenic receptor (EGF, IGF, c-MET, PDGF, FGF, VEGF), RAS/RAF/MAPK, PI3K/AKT/mTOR, and IL6/JAK/STAT (8)(9)(10)(11).…”
Section: Genetic Alterations and Molecular Targets In Hccmentioning
confidence: 99%
“…The non- proliferative subclass is correlated with better outcomes, lower AFP levels, and good-to-moderate differentiation. The proliferative subclass usually consists of HCC secondary to HBV, while the non-proliferative subclass consists of HCC secondary to HCV infection and alcoholic cirrhosis (7).…”
Section: Genetic Alterations and Molecular Targets In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have revealed etiological patterns and multiple genes/pathways signifying initiation and progression of HCC. These pathways include CTNNB1/WNT‐β‐catenin, TPp53, ARID1/2s, HGF/c‐Met, and vascular endothelial growth factor/angiogenic signaling 5, 6, 7, 8, 9, 10, 11, 12. However, unlike the transforming growth factor β (TGF‐β) pathway, loss of p53 and/or activation of β‐catenin do not spontaneously drive HCC in animal models 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%